1332Endometriosis, assisted reproductive technology and adverse pregnancy outcomes: a population based data linkage study. (2nd September 2021) - Ibiebele, Ibinabo; Nippita, Tanya; Baber, Rodney; Torvaldsen, Siranda
Abstract: Background: Endometriosis is a chronic inflammatory disease characterised by endometrial tissue outside the uterus – pain and infertility are common symptoms. There is a paucity of data on the association between endometriosis and adverse pregnancy outcomes where the contribution of assisted reproductive technology (ART) use is also considered. This study will examine the association between endometriosis, with and without ART use, on adverse pregnancy outcomes. Methods: Population data linkage study of all female NSW residents aged 15-45 years with a singleton birth in 2006-2015. Pregnancies were classified into 4 groups based on endometriosis diagnosis (yes/no) and ART use (yes/no). Multinomial logistic regression was used to estimate the odds of adverse pregnancy outcomes with 99% confidence intervals, adjusting for maternal and pregnancy factors. Outcomes assessed included placenta praevia, antepartum haemorrhage, planned birth (induction of labour or caesarean section) and preterm birth. Results: Of 889, 101 eligible pregnancies, women with endometriosis were more likely to be older while women who used ART were more likely to be nulliparous, birth in a private hospital and less likely to smoke. Adjusted odds ratios for selected study outcomes are outlined below. Conclusions: Endometriosis is associated with increased odds of preterm birth, placenta praevia, antepartum haemorrhage and planned birth. In general, the odds of adverse pregnancy outcomes associated with endometriosis were further increased with ART use. Key messages: These findings suggest that women with endometriosis, especially those who achieved pregnancy via ART use, represent a high risk obstetric population requiring appropriate surveillance and management.